THE INNOVATION PROCESS IN BUBALINE MILK PRODUCTION: A CASE STUDY IN THE CITY OF QUEIROZ / SP - Dadario, N.; Santini Pigatto, G.A.; Baptista, R.D. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Innovation has become paramount for small producers, since in order to stay in the current market it is necessary to increase productivity, improve the quality of the product offered and have a good management system for your business. In this way, the objective of this work is to analyze the types of innovations that a buffalo milk producing community in the city of Queiroz / SP realizes and what are the restrictive forces and the driving force for adopting innovations. For this, a qualitative approach was used in which producers were interviewed through field research. As results, it was identified that the most common innovations among producers are those related to process and organizational. Family influence, fears of financing and other internal and external activities to the propriety are factors that restrict the adoption of innovation, while the proximity between producers and the loss of the main purchasing agent of yours products are forces that drive this adoption. It was then realized that for the evaluated community the adoption of new technologies is fundamental so that it can remain in the buffalo milk market.